The Role of Value Judgements in Measuring Inequality - John Creedy; Jesse Eedrah (New Zealand Government, The Treasury, 2014)
When measuring inequality, value judgements are imposed, often implicitly, at several stages. In particular, the choice of `welfare metric', adult equivalence scale, unit of analysis and the inequality measure itself cannot avoid value judgements. This paper illustrates the effects of using different distributions and summary measures, using New Zealand data for the period 2007 to 2011. Using an annual accounting period, alternative welfare metrics and units of analysis are investigated. In addition, the sensitivity to assumptions about economies of scale within households is examined, and changes in inequality are decomposed into those arising from population and tax structure changes. When considering the period 2007 to 2010 all measures agree that inequality fell, although the extent of the reduction varies. For the period 2007 to 2011 (after the tax reforms of 2010) the answer to the question of whether inequality in New Zealand has risen or fallen depends crucially on the combination of welfare metric, income unit, adult equivalent scale and inequality measure used. In empirical studies it is therefore important to explore a wide range of alternative approaches, providing information for readers to make their own judgements.
Keywords: 330; Soziale Ungleichheit; Messung; Soziale Werte; Neuseeland